Sensitivity analysis of flexoelectric materials surrogate model based on the isogeometric finite element method - Li, Haozhi; Zhao, Juan; Guo, Xiaokun; Cheng, Yu; Xu, Yanmin; Yuan, Xiaohui (Frontiers in Physics, 2022)
In this paper proposes a sensitivity analysis method based on a Polynomial Chaotic Expansion (PCE) surrogate model for flexoelectric materials. The non-uniform rational B-splines (NURBS) basis functions to discretize the fourth-order partial differential equation for flexoelectricity and obtains a deterministic solution (electric potential). The mathematical expressions of surrogate model for the flexoelectric materials are established by considering uncertain parameters such as independent Young's modulus, concentrated load and flexoelectric constants. The sensitivity expression is found by derivation the mathematical expression for the surrogate model. Moreover，the finite difference method (FDM) are conducted in numerical examples to demonstrate the validity and correctness of the proposed algorithm.